Women leadership in higher education: Past, present and future trends - Muhammad Ashraf, Fauzi; Tan, Christine Nya-Ling; Puteri Fadzline, Muhamad Tamyez; Nurul Ashykin, Abd Aziz; Wider, Walton (Emerald Group Publishing Ltd., 2024)
Purpose: Gender bias and stereotypes are universal issues in today’s society. This study presents a comprehensive review of women’s leadership based on bibliometric analysis. The feminist approach to leadership is helpful in many ways, and it could be the type of leadership needed in the challenging world of academia. Women present unique characteristics and traits, particularly their motherly approach to leadership. Design/methodology/approach; A review of the literature based on bibliometric analysis by mapping the knowledge structure of the subject is conferred by uncovering the past, present and future trends based on three bibliometric analyses. Findings: The finding suggests that gender equality, stereotypes and barriers in women’s leadership are at the forefront of the subject in HEIs. The overall system, mindset and willingness for institutional transformation are needed to change the mindset of accepting women as leaders of HEIs. Research limitations/implications: This study brought the significant idea of increasing women’s empowerment in HEIs, eventually strengthening institutional leadership’s capability towards advanced education. Originality/value: This study would present a crucial foundation in women’s empowerment, particularly from the HEIs perspective and from the generic women’s leadership literature.